Conceptualizing Country-of-Ingredient Authenticity of Luxury Brands - Cheah, Isaac; Zainol, Zahirah; Phau, Ian (Elsevier, 2016)
The research investigates the influence of country-of-ingredient authenticity towards product judgement and ultimately how the construct influences the willingness to buy and recommend luxury branded products. This research is divided into 2 studies where the methodology takes on a 2 × 2 × 2 experimental research design looking at the raw materials acquired to craft Alpaca wool sweaters from brand and country of origin (COO) such as Prada (Made in Peru), Prada (Made in Italy) and Touchè (Made in Peru) and artisan skills used for Chikan-embroidered dresses from Prada (Made in India), Prada (Made in Italy) and Touchè (Made in India). Some findings indicate that Alpaca wool sweater ‘made in Peru’ does improve consumers' judgment of the branded product however country image and brand image played a part in authenticating the Chikan-embroidery that is ‘made in India’. Sustainable and ethical practices also positively improve product judgement of the products.